Improved Flame-Retardant and Ceramifiable Properties of EVA Composites by Combination of Ammonium Polyphosphate and Aluminum Hydroxide - Feipeng Lou (Polymers, 2019)
Ceramifiable flame-retardant ethylene-vinyl acetate (EVA) copolymer composites for wire and cable sheathing materials were prepared through melt compounding with ammonium polyphosphate (APP), aluminum hydroxide (ATH) and fluorophlogopite mica as the addition agents. The effects of ammonium polyphosphate, alumina trihydrate, and APP/ATH hybrid on the flame retardant, as well as on the thermal and ceramifiable properties of EVA composites, were investigated. The results demonstrated that the composites with the ratio of APP:ATH = 1:1 displayed the best flame retardancy and the greatest char residues among the various EVA composites. The tensile strength of the composites was 6.8 MPa, and the residue strength sintered at 1000 °C reached 5.2 MPa. The effect of sintering temperature on the ceramifiable properties, microstructures, and crystalline phases of the sintered specimen was subsequently investigated through X-ray diffraction, Fourier transform infrared, and scanning electron microscopy. The XRD and FTIR results demonstrated that the crystal structure of mica was disintegrated, while magnesium orthophosphate (Mg3(PO4)2) was simultaneously produced at an elevated temperature, indicating that the ceramization of EVA composites had occurred. The SEM results demonstrated that a more continuous and compact microstructure was produced with the rise in the sintering temperature. This contributed to the flexural strength improvement of the ceramics.